Application of black salve to a thin melanoma that subsequently progressed to metastatic melanoma: a case study - Sivyer, Graham W.; Rosendahl, Cliff (Dermatology Practical & Conceptual, 2014)
This is a case study of a female patient diagnosed with superficial spreading melanoma who decided to treat the lesion by the application of a preparation known as black salve. Persistence of the melanoma was documented five years later with subsequent evidence of metastatic spread to the regional lymph nodes, lungs, liver, subcutaneous tissues and musculature. A literature search has revealed one other case study of the use of black salve for the treatment of melanoma.